Toradora!. Vol. 3 - Takemiya, Yuyuko, 1978- (Seven Seas Entertainment, 2018)
"It's swimming season! But Ryuuji's hopes of a relaxing dip are shattered when another spat between Taiga and Ami escalates into a challenge--a no-holds barred swimming contest! The prize? The winner gets to claim Ryuuji for the summer! Ryuuji's none too keen on being spirited away by Ami, but if he wants Taiga to win, he's going to have to teach her to swim from scratch! And what happens if Taiga doesn't even want to win?"--Page 4 of cover.